Modelling of technical tactical actions as the management factor competitive process and preparation of basketball players of high qualification - Doroshenko, E. Y. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
Application of modelling indicators of technical-tactical actions in a control system of preparation and competitive process of basketball players is considered. In research the official statistical data of the European championship on basketball of 2013 is used. It is shown that modelling indicators of technical-tactical actions allow to form an optimum orientation of training process with application of specialised means at various stages of a year cycle of preparation, to supervise indicators of technical-tactical actions in competitive process. It is recommended as modelling to use following ranges of indicators of technical-tactical activity: (in one game): efficiency of two game point throws (44 48 %, throws in game in number 46 50); efficiency of three game point throws (35 39 %, throws in game in number 15 19); efficiency of penal throws (64 72 %, throws in game in number 16 21); indicators of a parity of the typed and passed points (1,2 1,3); ball selections (37 40); ball interceptions (6 10); goal passes (13 16); ball losses (12-14); the block-shot (2,5 3,0).